2013
DOI: 10.1352/1944-7558-118.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Memory Training Leads to Sustained Improvement in Visuospatial Short-Term Memory Skills in Children with Down Syndrome

Abstract: This study evaluated the impact of a computerized visuospatial memory training intervention on the memory and behavioral skills of children with Down syndrome. Teaching assistants were trained to support the delivery of a computerized intervention program to individual children over a 10-16 week period in school. Twenty-one children aged 7-12 years with Down syndrome were randomly allocated to either an intervention or waiting list control group. Following training, performance on trained and non-trained visuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 21 publications
6
108
1
Order By: Relevance
“…11 For example, a recent study demonstrated that training could enhance WM in children with Down syndrome. 12 These findings thus support the importance of early recognition of WM difficulties.…”
Section: Introductionsupporting
confidence: 53%
“…11 For example, a recent study demonstrated that training could enhance WM in children with Down syndrome. 12 These findings thus support the importance of early recognition of WM difficulties.…”
Section: Introductionsupporting
confidence: 53%
“…The implications of having no control group can dramatically influence the quality of reported training effects by inflating the amount of training benefits, and ignoring the possibility of naturally occurring improvements in line with development. Despite the fact that some studies have employed a more robust design to assess the efficacy of training such as randomized control trials, these studies often include waitlist/passive controls who do not receive any training or engage in alternative tasks (Beck et al, 2010;Bennett et al, 2013;Johnstone et al, 2011;Rabiner et al, 2010;Steiner et al, 2011;Tamm et al, 2013). Although this is preferable to no control group, it still remains difficult to assess whether observed improvements are the result of the training program, or whether they are simply the result of repetition effects or intervention effects (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Bennett et al (2013), Van der Molen and colleagues (2010) The inconsistencies in near transfer effects in training studies involving children with ID are further compounded by a lack of far transfer effects; with no improvements reported in reasoning skills (Soderqvist et al, 2012) or inhibitory control after training (Bennett et al, 2013;Van der Molen et al, 2010). The lack of far transfer effects as well as the variability in training success in children with ID may indicate that WM is not the most appropriate domain to target in order to produce extensive and stable cognitive change.…”
Section: Attention Training Vs Working Memory Training In Intellectuamentioning
confidence: 90%
See 1 more Smart Citation
“…The educational resources are cards made of cardboard only. The author considers that having multi-touch or physical elements is an interesting alternative to strengthen literacy skills [2].…”
Section: Methodsmentioning
confidence: 99%